DEPENDENCE, UNFREEDOM AND SLAVERY IN AFRICA: TOWARDS AN INTEGRATED ANALYSIS. (August 2016) - Rossi, Benedetta
Abstract : The three books reviewed in this article seek to provide interpretations of dependence, unfreedom and slavery in African societies. But they reach different conclusions; bring different methodological frameworks to bear on the circumstances they examine; and – when they are concerned with policy questions – propose different remedies. A comparison of these books is useful not only for understanding African dependence and unfreedom, but also for rethinking critically the approaches of some of the main contemporary strands of research on these phenomena.